Development of a Hypothetical Model of Multicultural Problem-Based Learning to Foster Tolerance Among Elementary School Students - Apip Rudianto; Galih Praja Wijaya (Universitas Sriwijaya in Collaboration with HDPGSDI (Himpunan Dosen PGSD Indonesia), 2026)
Social, cultural and religious diversity are characteristics of Indonesian society that call for the strengthening of tolerance through education. However, learning in schools still tends to be normative and cognitively oriented, meaning that the development of tolerance among pupils has not yet been optimal. This study aims to develop a hypothetical model of multicultural problem-based learning as a basis for fostering tolerance among pupils. This study employs a research and development approach within the framework of Educational Design Research. The research stages include needs analysis, the design of a hypothetical model, and conceptual validation through expert assessment. Data were collected through literature review, interviews, limited observation, and validation sheets, and were subsequently analysed using qualitative descriptive methods. The results indicate that the developed hypothetical model integrates problem-based learning principles with a multicultural context through structured learning syntax and mechanisms for the internalisation of tolerance values. This model is deemed conceptually sound and relevant as a foundation for the development of contextual and sustainable tolerance education.